Merger Control Law in Australia and New Zealand: Some Reflections on the Australian Reforms and Recent New Zealand Developments - Berry, Mark (Victoria University of Wellington Law Review, 2025)
There have been significant recent policy and case law developments relating to the application of competition law to mergers and acquisitions in New Zealand. This article is in two parts. The first addresses the current policy review into both procedural and substantive issues under pt 3 of the Commerce Act 1986. This policy review follows upon the detailed review of merger controls in Australia, which was completed at the end of 2024. The key process issue under the current review relates to the pre-notification of mergers to the Commerce Commission. It is argued that the current voluntary notification regime should be retained in New Zealand, despite the recent introduction of a mandatory notification regime in Australia. This article also traces the substantive changes which are open for consultation, the most significant being the extension of the substantial lessening of competition test to capture incremental increases in market power. The second part of this article provides critiques of two recent merger decisions of the Commerce Commission, namely the Serato and Foodstuffs decisions. This critique includes discussion of the Commerce Commission's approach to the assessment of mergers where there may be different competition effects over several markets. It is argued that the correct approach under s 47 of the Commerce Act in this setting is to apply a net competition test under which both the pro- and anti-competitive effects must be balanced.